Inovasi Digital Dalam Pemberdayaan UMKM Guna Mendorong Pembangunan Ekonomi Lokal Di Desa Klagen - Naura Bilqis Tasyakurina; Condro Widodo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Digital innovation has become an important aspect in efforts to empower MSMEs and develop local economies in various regions, especially Klagen Village. This research investigates the implementation and impact of digital innovation in the village context. Through a participatory approach, students explored how MSMEs in Klagen Village adopted digital technology such as creating a Linktree and MSME website, creating Google Maps points, and registering NIB to increase their market access and operational efficiency. The research results show that the adoption of digital innovation has made a significant contribution to increasing income, expanding product ranges, and accelerating MSME business processes. However, challenges such as limited knowledge and skills, concerns about data security, and the level of public acceptance were also identified as potential barriers. By exploring these findings, this activity not only provides insight into the benefits of digital innovation for MSMEs at the local level, but also highlights the importance of cross-sector collaboration to increase digital innovation and sustainable economic growth at the village level.